Chilblains-Like Lesions in Pediatric Patients: A Review of Their Epidemiology, Etiology, Outcomes, and Treatment - Fennell, Jessica; Onel, Karen (Frontiers in Pediatrics, 2022)
Vascular pathologies associated with SARS-CoV-2 infection are poorly understood. Color and sensory changes to the extremities, often referred to as “COVID toes” or chilblains-like lesions, have been widely reported in children and adolescents since the onset of the pandemic, raising the concern that they could be a vasculitis secondary to the infection. However, it is unclear if the lesions are a result of the infection or an epiphenomenon. Most literature focuses on adults, and while there are reports on children and adolescents, many of them are small. This review will help medical care providers better understand the epidemiology, etiology, outcomes, and potential treatments for chilblains-like lesions seen in children and adolescents during the pandemic.